The ejecting lamella of impacting compound droplets - Liu, Dongdong (2019)
Impacting dynamics of compound droplets consisting of oil and water–glycerol mixture transitions from spreading to splashing with an increasing volumetric oil-mixture ratio. The transition to splashing is directly related to the dynamics of the ejecting lamella upon impact. Here, we present a detailed study of the ejecting lamella at the early stage of the impact. We experimentally characterize the ejection velocity and time of the ejecting lamella for a wide range of impacting velocities, volumetric oil ratios, and viscosities of the mixture. We show that ejecting dynamics depends significantly on the volumetric oil-mixture ratio, while it is slightly affected by the viscosity of the mixture. We also propose and verify experimentally a predictive model for the ejection velocity and time of the lamella.